Prenatal exposure to synthetic phenols and phthalates and child respiratory health from 2 to 36 months of life - Coiffier, Ophélie; Lyon-Caen, Sarah; Boudier, Anne; Quentin, Joane; Gioria, Yoann; Pin, Isabelle; Bayat, Sam; Thomsen, Cathrine; Sakhi, Amrit K.; Sabaredzovic, Azemira; Slama, Rémy; Philippat, Claire; et al. (Environmental pollution (1987), 2023)
Exposure to phthalates and synthetic phenols is ubiquitous. Some of them are suspected to impact child respiratory health, although evidence still remains insufficient. This study investigated the associations between prenatal exposure to phthalates and phenols, individually and as a mixture, and child respiratory health assessed by objective lung function measures since 2 months of age. Among 479 mother-child pairs from the SEPAGES cohort, 12 phenols, 13 phthalate and 2 non-phthalate plasticizer metabolites were measured in 2 pools including each 21 urine samples collected at the 2nd and 3rd pregnancy trimesters. Lung function was measured at 2 months using tidal breathing flow-volume loops and nitrogen multiple-breath washout, and at 3 years using oscillometry. Asthma, wheezing, bronchitis and bronchiolitis were assessed by repeated questionnaires. A cluster-based analysis was applied to identify exposure patterns to phenols and phthalates. Adjusted associations between clusters as well as each individual exposure biomarker and child respiratory health were estimated by regression models. We identified four prenatal exposure patterns: 1) low concentrations of all biomarkers (reference, n = 106), 2) low phenols–moderate phthalates (n = 162), 3) high concentrations of all biomarkers except bisphenol S (n = 109), 4) high parabens–moderate other phenols–low phthalates (n = 102). At 2 months, cluster 2 infants had lower functional residual capacity and tidal volume and higher ratio of time to peak tidal expiratory flow to expiratory time (tPTEF/tE) and cluster 3 had lower lung clearance index and higher tPTEF/tE. Clusters were not associated with respiratory health at 3 years but in the single-pollutant models, parabens were associated with increased area of the reactance curve, bronchitis (methyl, ethyl parabens) and bronchiolitis (propyl paraben). Our results suggested that prenatal exposure to mixtures of phthalates reduced lung volume in early life. Single exposure analyses suggested associations of parabens with impaired lung function and increased risk of respiratory diseases. [Display omitted] •457 mother-child pairs with early and objective children's respiratory measurements.•Phenols and phthalate biomarkers measured in 2 pools of 21 urine samples each.•Children were clustered into patterns of prenatal exposure to the chemical mixture.•Prenatal phthalates, parabens and bisphenol S might impact child respiratory health.